2019
DOI: 10.1002/phar.2204
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 rs352139 Genetic Variant Promotes Tacrolimus Elimination in Chinese Liver Transplant Patients During the Early Posttransplantation Period

Abstract: Background There are limited markers that could facilitate individualized tacrolimus treatment in the early posttransplantation period. Genetic factors have been found to play critical roles in determining tacrolimus pharmacokinetics. Objective We aimed to examine the association of donor and recipient Toll‐like receptor (TLR) polymorphisms with tacrolimus elimination and the potential mechanism for TLR gene polymorphism–mediated tacrolimus metabolism. Methods Two independent cohorts including 297 patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…TLR9-rs352139 AA genotype carriers were thus protected from the effects of ischemia-reperfusion-induced inflammation, which resulted in conservation of their metabolic capacity. The opposite effect was observed for carriers of the TLR4-rs1927907-GG phenotype who exhibited higher tacrolimus C/D ratios than AA/AG carriers, indicating that these patients were more susceptible to the effects of inflammation on their drug-metabolizing capacity [91,92]. These studies illustrate that genetic variants in receptors can be important modulators of inflammation, which may be particularly relevant for receptors (e.g., IL6R or IL-1R) that are directly involved in the downregulation of CYP enzymes, but this remains to be investigated.…”
Section: Genetic Variation: Inflammatory Receptorsmentioning
confidence: 89%
See 1 more Smart Citation
“…TLR9-rs352139 AA genotype carriers were thus protected from the effects of ischemia-reperfusion-induced inflammation, which resulted in conservation of their metabolic capacity. The opposite effect was observed for carriers of the TLR4-rs1927907-GG phenotype who exhibited higher tacrolimus C/D ratios than AA/AG carriers, indicating that these patients were more susceptible to the effects of inflammation on their drug-metabolizing capacity [91,92]. These studies illustrate that genetic variants in receptors can be important modulators of inflammation, which may be particularly relevant for receptors (e.g., IL6R or IL-1R) that are directly involved in the downregulation of CYP enzymes, but this remains to be investigated.…”
Section: Genetic Variation: Inflammatory Receptorsmentioning
confidence: 89%
“…Therefore, it has been postulated that genetic variability in TLRs may alter the effect of inflammation and its consequences for drug metabolism. Ou et al showed that liver transplant patients with the TLR9-rs352139 AA genotype exhibited lower C/D tacrolimus levels than carriers of the AG/GG genotype [91]. Subsequent cellular experiments provided functional support for these observations and demonstrated that the TLR9-rs352139 variant impaired TLR9 expression and consequently reduced NF-κB activation.…”
Section: Genetic Variation: Inflammatory Receptorsmentioning
confidence: 99%
“… 11 , 12 Enzymes in the cytochrome P450 (CYP) 3A family are responsible for the oxidative metabolism of tacrolimus. 13 Numerous studies have demonstrated the importance of the genetic variation (rs776746, or ∗3) of CYP3A5 gene in tacrolimus metabolism. 14 , 15 Recent guidelines for the use of tacrolimus proposed by the Clinical Pharmacogenetics Implementation Consortium (CPIC) provide preliminary suggestions relevant to the rs776746 genotype and tacrolimus dosing.…”
Section: Introductionmentioning
confidence: 99%